Evaluation of Major Risk Factors And Metabolic Syndrome Criteria In Predicting Coronary Artery Disease Risk - Nagihan Beştepe; Ömer Dönderici; Burcu Demirkan (Ankara Medical Journal, 2020)
INTRODUCTION: The concept of metabolic syndrome (MS) is critical due to the underlying insulin resistance (IR) and included risk factors for cardiovascular disease. In this study, we aimed to investigate the value of MS criteria in predicting cardiovascular risk as well as traditional cardiovascular risk factors. METHODS: The study was performed on 264 patients who underwent coronary angiography (CAG) for diagnostic purposes. According to the CAG result, patients with significant stenosis in one or more coronary arteries were considered the CAD (coronary artery disease) group, and cases without stenosis were accepted as the control group. CAD and control groups were compared in terms of traditional risk factors and MS criteria. The traditional risk factors and MS were evaluated for the patients by regression analysis and risk predictions were calculated. RESULTS: There were 103(39.01%) female and 161(60.98%) male patients. The mean age was57.91+-9.97 in females and 58.63+-10.21 in males. Considering the incidence of MS criteria, the elevation of waist circumference(WC) in women, low HDL-C in men, and high TG in both sexes were at the forefront.MS was not significant in predicting CAD risk but every 1 cm increase in WC resulted in increased risk of CAD in both sexes and every 1 cm increase in hip circumference(HC) resulted in decreased risk of CAD. DISCUSSION AND CONCLUSION: In our study, we observed that MS appeared with high WC in women and low HDL-C in men. While this supports the assumption that low HDL-C is a feature of our ethnicity, new studies are needed to determine MS criteria closely related to cardiovascular events in our society, especially in terms of HDL-C and WC.